AI in fashion industry - Banerjee, Satya; Mohapatra, Sanjay; Bharati, M. (Emerald points., 2022)
Fashion is a glamorous industry, one of beauty, money, fame, and huge profits. However, from the inside, it is clear the industry is suffering. An industry worth $3 Billion (USD), the fashion industry is characterized by products with a short shelf-life, wrong forecasts, low profits, and ever-increasing competition. On the periphery, technology is rapidly invading the fashion industry, with emerging forms such as Artificial Intelligence, Machine Learning, Deep Learning, Artificial Neural Networks, Human-Robot Interface, making their way into this industry in recent years. AI in Fashion Industry discusses recent developments in fashion forecasting, developing a 'framework of AI-based fashion forecasting' and validates the framework with a qualitative case study of the world's first fashion intelligence company based in Bengaluru, India. This book studies the relationship between fashion and social media engagement of consumers, before moving on to create a 'conceptual framework of fashion e-forecasting.' The case study addresses the forecasting-based business problem of a family-owned fashion retail business. This book is unique, suggesting a novel method of fashion product development in the light of data-driven intelligence; documenting some of the rapid developments in the field with the onset of technology and addressing some of the fundamental questions that are becoming more relevant in recent years.